Georgia Architectural and Historic Properties Survey of 716 Jackson Street, Valdosta, Ga. - Smith, Bartholomew; Smith, Freda (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of 716 Jackson Street, Valdosta, Ga. December 1980. One story L-shaped, multi-gabled roof house. Shed porch with square posts, interior chimney, set on brick piers; double hung sash windows with 2/2 lights. Fair condition. Date of Construction: App. 1905-1915. Typical vernacular house much like others in the same area built around the same time. Has significance as part of a potential N.R. district.
Georgia Architectural and Historic Properties Survey of 716 Jackson Street, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 3 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 80.8 MB (84,729,929 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Valdosta (Ga.)